KETERLIBATAN ANGGOTA SEBAGAI FONDASI EFEKTIVITAS ORGANISASI: ANALISIS PERAN KOMUNIKASI INTERNAL, KONTRAK PSIKOLOGIS, DAN DUKUNGAN ORGANISASI - Ahmad Yafi Fairuzzuhair; S. Rouli Manalu (Interaksi Online, 2026)
This study examines the effect of internal communication satisfaction (ICS) on member engagement in student organizations and investigates the mediating roles of psychological contract fulfillment (PCF) and perceived organizational support (POS). A quantitative explanatory approach was employed through a survey of 324 active students at Universitas Diponegoro who were members of intra-campus student organizations. Data were analyzed using PLS-SEM with a Reflective-Reflective Higher-Order Construct specification and the Disjoint Two-Step Approach. Findings indicate that ICS has a positive and significant effect on member engagement (β = 0.452, p < 0.001, f² = 0.184). POS significantly mediates the ICS engagement relationship (β = 0.182, p < 0.001), while PCF does not serve as a significant mediator (β = 0.012, p = 0.772). The model demonstrates moderate predictive capability (R² = 0.459). The study concludes that member engagement is driven more by experienced relational support than by evaluations of fulfilled initial expectations.